Streamlining IT Help Desk and Incident Management: Harnessing the Power of the ITIL Framework for Enhanced Efficiency in IT Services - Alfonsus Fero Jaya Nugroho; Melissa Indah Fianty (Universitas Bina Darma, 2023)
This study examines the potential of leveraging incident management and IT Helpdesk principles from ITIL V3 to enhance the daily operations of an IT division. The research involved collecting email communication data between users and the IT division, as well as conducting interviews with individuals associated with the IT division and various company employees. The ITIL Maturity Level (ITML) method was utilized to analyze the findings, revealing that IT Helpdesk achieved a score of 3.5 (Quality Control), while incident management received a score of 2 (Process Capability). However, both areas fell short of meeting the requirements for level 3 (Products) according to the ITIL Self-Assessment table, resulting in a classification of